Heat Transfer Research on Food Frozen by Cryogenic Liquid Nitrogen - Fang Jinlin; Liu Jianhua; Liang Yaying; Zhou Xiaoqing (Zhileng xuebao)
To study the heat-flux change and cooling rate in the freezing and heat-transfer process of liquid nitrogen, a low-temperature liquid-nitrogen experimental device was made. It was based on the idea of the direct contact heat exchange with the food after the liquid nitrogen vaporized. The experiment was conducted at seven temperature regions ranging from ﹣50 ℃ to ﹣170 ℃ with ﹣20 ℃ interval. A potato was frozen from the initial temperature 18 ℃ to the freezing point ﹣18 ℃. The average heat flux and the temperature distribution of the heat-transfer process were calculated using a curve-fitting formula. The heat-flux change and temperature change rate were analyzed to obtain the most appropriate nitrogen temperature. The results show that when the nitrogen temperature is ﹣122.87 ℃, the heat-flux growth rate reaches the maximum. As the temperature continues to reduce, the heat-flux growth rate decreases; at this point, part of the heat gathered internally from the food results in wasted energy. The temperature change rate for different interfaces was calculated when the food-center temperature was ﹣3 ℃, and the optimum nitrogen temperature was found to be ﹣133.11 ℃. This was only 6.71% different from the previous result. Thus, the optimum nitrogen-freezing temperature is about ﹣128 ℃, which can ensure the rapid freezing of the food and improve the effective utilization of the nitrogen.